Synergistic effects of sodium butyrate and cisplatin against cervical carcinoma in vitro and in vivo - Chu, Huijun; Sun, Xiaoyuan; Wang, Jia; Lei, Ke; Shan, Zhengyi; Zhao, Chenyang; Ning, Ying; Gong, Ruining; Ren, He; Cui, Zhumei (Frontiers in Oncology, 2022)
Backgrounds: Cisplatin-based chemotherapy has been considered as the pivotal option for treating cervical cancer. However, some patients may present a poor prognosis due to resistance to chemotherapy. As a metabolite of natural products, sodium butyrate (NaB) could inhibit the proliferation of several malignant cells, but little is known about its combination with cisplatin in the treatment of cervical cancer. Materials and Methods: Flow cytometry, CCK-8 assay, and Transwell assay were utilized to analyze the cellular apoptosis, viability, cellular migration and invasion upon treating with NaB and/or cisplatin. The allograft mice model was established, followed by evaluating the tumor volume and necrotic area in mice treated with NaB and/or cisplatin. Western blot was performed for detecting protein expression involved in epithelial-mesenchymal transition (EMT) and the expression of MMPs. Immunohistochemical staining was conducted with the tumor sections. The transcription, expression, and cellular translocation of β-catenin were determined using luciferase reporter gene assay, Real-Time PCR, Western blot, and confocal laser scanning microscope, respectively. Results: NaB combined with cisplatin inhibited cell viability by promoting apoptosis of cervical cancer cells. In vivo experiments indicated that NaB combined with cisplatin could inhibit tumor growth and induce cancer cell necrosis. Single application of NaB activated the Wnt signaling pathway and induced partial EMT. NaB alone up-regulated MMP2, MMP7 and MMP9 expression, and promoted the migration and invasion of cervical cancer cells. The combination of cisplatin and NaB inhibited cellular migration and invasion by abrogating the nuclear transition of β-catenin， reverse EMT and down-regulate MMP2, MMP7 and MMP9. Immunohistochemical staining indicated that NaB combined with cisplatin up-regulated the expression of E-cadherin and reverse the EMT phenotype in the mice model. Conclusions: NaB serves as a sensitizer for cisplatin, which may be a promising treatment regimen for cervical cancer when combined both. NaB alone should be utilized with caution for treating cervical cancer as it may promote the invasion and migration of cervical cancer cells.